Toughening Effect of Liquid Natural Rubber on The Morphology and Thermo-Mechanical Properties of the Poly(Lactic Acid) Ternary Blend - Mohd Bijarimi, Mat Piah; Sahrim, Ahmad; A. K. M., Moshiul Alam (Springer Berlin Heidelberg, 2017)
In this work, poly(lactic acid) (PLA) was melt blended with liquid natural rubber (LNR) and linear low-density polyethylene (LLDPE) to fabricate a PLA–LNR–LLDPE ternary blend. The torque rheology demonstrates the melt mixing behavior of PLA–LLDPE binary and PLA–LNR–LLDPE ternary blends. Mechanical properties of ternary blend illustrate the highest toughness as compared to neat PLA and PLA–LLDPE binary blend. Fracture morphology reveals the plastic deformation behavior in the ternary blend which is illustrated in TEM micrograph. The cold crystallization temperature of the ternary blend appears at a lower temperature as compared to the binary blend. The thermal stability of PLA is improved due to blending with LLDPE and LNR. The ternary blend exhibits greater storage modulus in the glassy state as well as in the rubbery state as compared to neat PLA and binary blend. Finally, LNR performed as an effective compatibilizer between PLA and LLDPE.